A two-stage model of peer influence in adolescent substance use: Individual and relationship-specific differences in susceptibility to influence (vol 28, pg 1243, 2003) - Urberg, KA; Luo, Q; Pilgrim, C; Degirmencioglu, SM (Pergamon-Elsevier Science Ltd, 2004)
[Abstract Not Available]